Deletion of five residues from the coiled coil of fibrinogen (Bβ Asn167_Glu171del) associated with bleeding and hypodysfibrinogenemia - Stephen O. Brennan; Ryan L. Davis; Robin Lowen; Anna Ruskova (Haematologica, 2009)
Routine pre-surgical coagulation investigations led to the detection of a novel type of hypodysfibrinogenemia whose functional defect appears to result from an alteration in the spacing between the functional domains of the fibrinogen molecule. The detection, by reverse phase HPLC, of a minor isoform of Bβ chain with a 554 Da decrease in mass led to the identification of a deletion of five amino acids (NVVNE) from the center of the coiled coil. The variant chain contributed only 10% of the total Bβ material and the mutation (BβAsn167_Glu171del) was associated with both increased clotting times and low functional and physical fibrinogen concentrations in 3 family members. There was a significant history of pregnancy-associated bleeding and miscarriage within the first trimester. Mechanistically the 15-nucleotide deletion appears to arise from replication advancement during DNA synthesis caused by a flanking pentanucleotide repeat of AATGA.